2019
DOI: 10.7554/elife.46607
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila model of neuronal ceroid lipofuscinosis CLN4 reveals a hypermorphic gain of function mechanism

Abstract: The autosomal dominant neuronal ceroid lipofuscinoses (NCL) CLN4 is caused by mutations in the synaptic vesicle (SV) protein CSPα. We developed animal models of CLN4 by expressing CLN4 mutant human CSPα (hCSPα) in Drosophila neurons. Similar to patients, CLN4 mutations induced excessive oligomerization of hCSPα and premature lethality in a dose-dependent manner. Instead of being localized to SVs, most CLN4 mutant hCSPα accumulated abnormally, and co-localized with ubiquitinated proteins and the prelysosomal ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 97 publications
5
30
0
Order By: Relevance
“…These mutations result in either a substitution of Leu115 to Arg (L115R) or the deletion of Leu116 (ΔL116), both of which are located within the CS domain ( Figures 1A,B ). Recent studies suggest that these mutations reduce CSPα palmitoylation while increasing its aggregation propensity ( Benitez and Sands, 2017 ; Diez-Ardanuy et al, 2017 ; Imler et al, 2019 ; Naseri et al, 2020 ). Additionally, these mutations cause the mis-localization of the mutant proteins in cells ( Imler et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These mutations result in either a substitution of Leu115 to Arg (L115R) or the deletion of Leu116 (ΔL116), both of which are located within the CS domain ( Figures 1A,B ). Recent studies suggest that these mutations reduce CSPα palmitoylation while increasing its aggregation propensity ( Benitez and Sands, 2017 ; Diez-Ardanuy et al, 2017 ; Imler et al, 2019 ; Naseri et al, 2020 ). Additionally, these mutations cause the mis-localization of the mutant proteins in cells ( Imler et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in this gene cause the only autosomal dominant form among the NCLs [ 83 , 84 ]. Imler and colleagues [ 85 ] generated two fruit fly models of CLN4 through P-element insertion of the mutated human CSPα (hCSPα) in the first model and of the mutated Drosophila CSPα (dCSPα) in the second one. The hCSPα in Drosophila is correctly palmitoylated and efficiently traffics to exon terminals, where it co-localizes with endogenous dCSPα.…”
Section: Current Drosophila Models Of Lsds: An mentioning
confidence: 99%
“…Expression of the normal hCSPα restores adult lifespan, meaning that the protein has a conserved function in the fly and expression of the normal dCSPα only partially rescues adult lifespan. Therefore, they concluded that both models replicated the key hallmarks of the human pathology, while the study of these models allowed to find new insights into mechanisms underlying the pathology [ 85 ].…”
Section: Current Drosophila Models Of Lsds: An mentioning
confidence: 99%
“…Loss-of-function mutations in CSPα cause the lysosomal storage disorder adult-onset neuronal ceroid lipofuscinosis (ANCL) or Kufs disease (Benitez et al, 2011;Cadieux-Dion et al, 2013;Nosková et al, 2011;Velinov et al, 2012). Specifically, loss of CSPα function leads to progressive accumulation of lysosomes containing undegraded material such as lipofuscin/residual bodies, in ANCL patient brains (Benitez et al, 2011), in CSP -/mouse brains (Fernández-Chacón et al, 2004), in Drosophila models carrying the ANCL mutations (Imler et al, 2019), and in ANCL patient-derived induced neurons (Naseri et al, 2020). Tg-αSyn A53T /CSPα -/mice also accrue lysosomal proteins such as Lamp1 and cathepsin-L, as well as ATP5G -a mitochondrial protein characteristically stored in lysosomes of CSPα loss-of-function models and ANCL patient neurons (Supplementary Fig.…”
Section: Pathologenic Species Of αSyn Accumulate Within the Lysosomes Of Transgenic αSyn A53t Mouse Brainsmentioning
confidence: 99%